Dosimetric analysis of intraocular hemorrhage in nonsquamous head and neck cancers treated with carbon-ion radiotherapy. (May 2022) - Nachankar, Ankita; Musha, Atsushi; Kubo, Nobuteru; Kawamura, Hidemasa; Okano, Naoko; Sato, Hiro; Okada, Kohei; Adachi, Akiko; Ohno, Tatsuya
Highlights: First study investigating intraocular hemorrhage following carbon-ion radiotherapy. V40 and Dmax doses to eyeballs and retina are predictors of intraocular hemorrhage. Maxillary sinus primary and younger age are risk factors for intraocular hemorrhage. Abstract: Background and purpose: Carbon-ion radiotherapy is an attractive treatment option for unresectable/inoperable, nonsquamous cancers of the head and neck. Intraocular hemorrhage associated with carbon-ion radiotherapy for head and neck cancer is largely an unresearched area; hence, we investigated its incidence and predictive factors. Material and methods: We evaluated 79 patients (i.e., 158 eyes) with nonsquamous cancers of the head and neck treated by carbon-ion radiotherapy with a follow-up period of ≥12 months. Dosimetric parameters such as Dmax, Dmean and Vd [volume irradiated with "d" Gy (RBE)] and age, gender, primary site, histology and comorbidities were analyzed as predictors of intraocular hemorrhage. Results: Seven (8.9%) of 79 patients (158 eyes) developed intraocular hemorrhage with a median latent period of 24 months (range, 15–47 months). The 5-year cumulative incidence of intraocular hemorrhage was 6%. Dmax and V10–60 for eyeballs, retina and optic nerves were significantly higher in intraocular hemorrhage group than the rest ( p <0.001 for Dmax and V10–60 ). On univariate analysis, V40 ≥0.83 cm 3 and ≥0.66 cm 3 ( p = 0.001) and Dmax ≥54.75 Gy (RBE) and ≥54.58 Gy (RBE) ( p = 0.002) for eyeball and retina, respectively, were predictors of intraocular hemorrhage. Additionally, maxillary primary ( p = 0.025) and younger age (age <60 years, p = 0.048) were significant risk factors for intraocular hemorrhage. Conclusions: Dosimetric parameters such as V40 and Dmax for the eyeball, retina and maxillary sinus primary and younger age were significant predictors of intraocular hemorrhage following carbon-ion radiotherapy.